2020
DOI: 10.1002/slct.202003654
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, In Silico Studies and In Vitro Anticancer Activity of 3‐(4‐Methoxyphenyl)azetidine Derivatives

Abstract: A series of 3‐(4‐methoxyphenyl)azetidine analogues were synthesized and screened for their in vitro anticancer activity against nine different human cancer cell lines using the cell counting kit‐8 (CCK‐8) assay. The synthesized molecules were characterized by 1H NMR, 13C NMR, LCMS and IR analysis. The toxicity, bioavailability and lipophilicity of all the synthesized compounds were predicted by using osiris and molinspiration model. Molecular docking study revealed that, compound 6‐(3‐(3‐(2‐aminopyridin‐4‐yl)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…cell lines were seeded in 96 well plate and incubated for 24 h to achieve its morphology as showed in Figure 1. Post CCK 8 assay [43] it was observed that the ethyl 2‐(2‐(4‐((2‐ethoxyphenyl)carbamoyl)piperazin‐1‐yl)acetamido)‐5‐methyl‐4‐phenylthiophene‐3‐carboxylate (AP‐C12) extract showed highest inhibition in U87‐MG cell line. The inhibition was compared with the positive control Temozolomide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cell lines were seeded in 96 well plate and incubated for 24 h to achieve its morphology as showed in Figure 1. Post CCK 8 assay [43] it was observed that the ethyl 2‐(2‐(4‐((2‐ethoxyphenyl)carbamoyl)piperazin‐1‐yl)acetamido)‐5‐methyl‐4‐phenylthiophene‐3‐carboxylate (AP‐C12) extract showed highest inhibition in U87‐MG cell line. The inhibition was compared with the positive control Temozolomide.…”
Section: Resultsmentioning
confidence: 99%
“…cell lines were seeded in 96 well plate and incubated for 24 h to achieve its morphology as showed in Figure 1. Post CCK 8 assay [43]…”
Section: In Vitro Cytotoxicity Studiesmentioning
confidence: 99%
“…Thus, their design and synthesis serve as a key part of synthetic chemical research. [ 33 ] In among varieties of heterocycles, azetidines constitute a vital and very significant place but the least explored group. The azetidine skeletons displayed a good balance between molecular rigidity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33,34 ] This ring permits an effectual modification of pharmacological properties [ 35 ] and that's why azetidine serves as a core part of many existing drugs such as azelnidipine, tebanicline, delafloxacin, baricitinib, cobimetinib, and tebipenem. [ 33 ] In the earlier research, [ 36 ] it was illustrated that azetidine moiety as a linker with phenyl ring act as a pharmacophore. Thiazole‐containing skeletons are one of the most revered skeletons and key pharmacophores with many applications and pharmacological activities attributed to them such as antimicrobials, [ 37 ] antioxidant, [ 38 ] anticandida and cytotoxicity, [ 39 ] and anti‐inflammatory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation